Implementasi Manajemen Berbasis Sekolah Dalam Meningkatkan Efektivitas Kinerja Kepala Sekolah SMP Islam Terpaddu Ruhul Islam Simeulue - Syarul Amin ZD (UMSU, 2023)
To implement school-based management at SMP Islam Terpadu Ruhul Islam This research is aimed at Simeulue. To increase the effectiveness of the performance of school principals at SMP Islam Terpadu Ruhul Islam Simeulue. To find out and analyze the Implementation of School Based Management in increasing the effectiveness of the performance of school principals at SMP Islam Terpadu Ruhul Islam Simeulue. Research results How important and big is the role of the school principal in every decision making to determine policy steps for the interests, needs and development of schools in a better direction. Another view of the role and function of the school principal in teacher development. In fostering discipline carried out by the principal, it has not been implemented optimally because there is still a lack of firmness by the principal in fostering teacher discipline, but the exemplary attitude has been shown by the principal. The leadership of the Simeulue Islam Terpadu Middle School Principal in completing assignments and work is in accordance with the set time in improving teacher performance by carrying out routine supervision. The task of the school principal in supervising teacher performance has indeed been carried out, but it has not been fully maximized. This will have implications for improving teacher performance in the school because there will be ups and downs in teacher performance and this will affect the learning process for students. schools productively in accordance with the provisions that have been set in improving teacher performance for the realization of the work of teachers and principals of SMP Islam Terpadu Ruhul Islam Simeulu